PENGARUH PEPTON TERHADAP PERTUMBUHAN EMBRIO ANGGREK Vanda tricolor Lindley var. Suasiv ASAL MERAPI SECARA IN VITRO - Rizka Riliant Puspasari; Ikhsanudin Nur Rosyidi; Eka Fitriana Candra Ningrum; Endang Semiarti (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
Orchidaceae is a valuable ornamental plant in Indonesia’s export commodities. The growth of orchid in nature is prolonged due to its microscopic size of the seed and has no endosperm. In the mass-production, an inducer is required to accelerate the growth in an in-vitro culture, one of which is peptone. The embryos used in this study is Merapi endemic orchid, the Vanda tricolor Lindley var. Suavis. This study aimed to determine the effect of peptone on the growth of eight weeks old of Vanda tricolor Lindley var. Suavis embryos and to determine the optimal peptone concentration to induce the growth of the orchid embryo. This experiment was conducted in the Biotechnology Laboratory of the Faculty of Biology Universitas Gadjah Mada from September to October 2016. The treatments applied in this study was a variety of peptone concentrations (0–3 g/L) in growth media to induce eight weeks old protocorm subcultures. The study measured the morphological development of protocorm to determine the effect. The results showed a positive effect of peptone on the growth of orchid embryos at the NP1 treatment concentration of 1 g/L. The growth reached the phase 6 with the rate measured about 6.85±0.001% in the fourth week. This value was higher than the protocorm growth rate when it reached the phase 6 in the fourth week on the NP0 medium measured at 5.22±0.003%, on the medium NP2 at 1.15±0.002%, and on the medium NP3 at 1.02±0.001%. This result showed the effect of peptone concentration to induce the growth of Vanda tricolor Lindley var. Suavis embryo, but the excess concentration of peptone inhibited the growth of protocorm.